The Power of Click: The Consumer and the New Ways of Digital Advertising - Ferro, Ximena (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2015)
The use of the new digital media has forced consumers to develop new physical and psychological abilities as well as brands have adapted their messages to the media that the public is using.